Determining The Dynamics of The Petroleum Buffer Reserve of Indonesia - Prima, Andry; Moengin, Parwadi; Astuti, Pudji; Sari, Emelia; Nugrahanti, Asri; Jawaid Butt, Osama (Testing Center for Oil and Gas LEMIGAS, 2026)
This study develops an integrated system dynamics and probabilistic Monte Carlo simulation framework to evaluate Indonesia’s Petroleum Buffer Reserve (PBR) strategy in alignment with Perpres 96/2024 and the nation’s broader energy security agenda. Monte Carlo simulation results reveal that only the scenario characterized by full import availability is capable of achieving the mandated 10.17-million-barrel reserve target, while all other scenarios consistently fail to accumulate sufficient stock under uncertainty. The probabilistic analysis further shows that this scenario yields a probability exceeding 98% of meeting or surpassing the target, in contrast to the near-zero success rates observed under restricted import conditions. Days-of-cover optimization highlights an additional strategic vulnerability: the current PBR target corresponds to only about 12 days of crude import protection. Building on the system’s dynamic behavior, this study recommends a minimum reserve target of 30 days as an immediately achievable benchmark. A 60-day reserve is identified as a feasible medium-term objective, provided that replenishment rates and storage capacity are enhanced. Achieving a 90-day reserve, consistent with international strategic stockpiling standards, would require substantial investment and diversification of supply sources. These findings underscore Indonesia’s structural dependence on imported crude oil and emphasize the need for assertive replenishment policies to strengthen national energy resilience